A novel spatial-resolution targeted metabolomics method in a single leaf of the tea plant (Camellia sinensis). (1st May 2020) - Dai, Weidong; Hu, Zhengyan; Xie, Dongchao; Tan, Junfeng; Lin, Zhi
Highlights: A spatial-resolution targeted metabolomics method in a single tea leaf was developed. The spatial resolution of the method is 1.7 × 1.7 mm 2 . Within-leaf distributions of 56 endogenous metabolites were determined. Astringent compounds may be involved in the tea plant response to the wounding. Abstract: In this study, a novel spatial-resolution targeted metabolomics method was developed for a single leaf on the basis of microscale sample preparation and dansylation derivatization coupled with ultraperformance liquid chromatography-tandem mass spectrometry with a spatial resolution of 1.7 × 1.7 mm 2 . The practicability of this method was demonstrated by providing absolute quantitative within-leaf distribution information for 56 endogenous metabolites (including 8 catechins, 2 alkaloids, theanine, 4 theaflavins, 14 flavonol/flavone and their glycosides, 21 amino acids, and 6 phenolic acids). An application of this method in a mechanically pierced tea leaf indicated that astringent catechins, quercetin, and quercetin glycosides may be involved in the tea plant response to the wounding. In conclusion, the proposed novel method offered richest information on the within-leaf distribution of metabolites in tea to date and will be greatly helpful in understanding the defensive responses of tea plants against biotic and abiotic stresses.